Road Quality and Mean Speed Score - Moszoro, Marian; Soto, Mauricio (Washington, D.C. : International Monetary Fund, 2022)
We introduce a novel measure of cross-country road quality based on the travel mean speed between large cities from Google Maps. This measure is useful to assess road infrastructure and access gaps. Our Mean Speed (MS) score is easier to estimate and update than traditional gauges of road network quality which rely on official reports, surveys (i.e., World Economic Forum's Quality of Roads Perception survey), or satellite imaging (i.e., World Bank's Rural Access Index). In a sample of over 160 countries, we find that MS scores range between 38 km/h (23.6 mph) and 107 km/h (66.5 mph). We show that the MS score is a strong proxy for road quality and access.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economic Development; Housing; National Government Expenditures and Related Policies; Other Public Investment and Capital Stock; Railroads and Other Surface Transportation